Monday

December 22, 2014

December 22, 2014

Posted by **Jayden Haddy** on Saturday, August 3, 2013 at 11:23am.

x(square) - 4(square root 5)x =6 = 0

Then x= or x=

- maths -
**Steve**, Saturday, August 3, 2013 at 2:09pmx^2 - 4√5 x + 6 = 0

x^2 - 4√5 x + (2√5)^2 + 6 - (2√5)^2 = 0

(x - 2√5)^2 = 14

x - 2√5 = ±√14

x = 2√5 ± √14

**Answer this Question**

**Related Questions**

maths - Consider the equation x(square) + 4px + 2q = 0 where p and q are real ...

Algebra - Use the quadratic formula to solve the equation. Give exact answers: ...

Math simplifying mixed radicals - Please help me simplify these following mixed ...

Algebra - Which of the following statements is true? A. Any quadratic equation ...

Math ~CHECK MY ANSWER~ - 1) Which of these is a rational number? a. Pi b. Square...

Math simplifying mixed radicals - Please help me simplify these following mixed...

Math ~CHECK MY ANSWERS~ - 1) Which of these is a rational number? a. Pi b. ...

Algebra - Rationalize each expression by building perfect nth root factors for ...

maths - solve the following equation by completing the square x(square) -13x + ...

maths - solve the following equation by completing square x(square) + 5x - 84 ...